MENINGKATKAN AKTIVITAS, KERJASAMA, DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL BATIK DI SEKOLAH DASAR - Madina, Nurul; Jannah, Fathul (Universitas Negeri Medan, 2024)
Abstract: The problem in this study is the low activity, cooperation, and learning outcomes of students in learning Mathematics. The purpose of the study describes the activity of educators, analyzes the increase in activity, cooperation and learning outcomes of students . This type of research uses PTK. The research subject of grade VI students of SDN Seberang Mesjid 5. The research was conducted in 3 meetings. The type of data used is qualitative as well as quantitative. The results showed that educator activity increased to reach a score of 28